14. HYSICAL ACTIVITIES OF STUDENTS OF HANOI MEDICAL UNIVERSITY AND SOME FACTORS RELATED IN 2022 (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the level of physical activity students at Hanoi Medical University are nowengaging in in 2022 and conduct some associated factor analysis.Methods: A cross-sectional descriptive study on 306 students of Hanoi Medical University using theIPAQ-SF toolkit. Classification and assessment of physical activity based on IPAQ-SF and WHOrecommendations.Results: Among the study subjects, 39 students (12.8%) were physically active at a high level, 118students were moderately active (38.6%) and 149 students were active at a low level (48.7%). Only35.3% of students are physically active in accordance with WHO recommendations. Physical activitywas statistically significantly correlated to 4 factors gender, school year, BMI, and significance.Conclusion: Students at Hanoi Medical University continue to exhibit comparatively low levels ofmental activity. The school may take action to increase extracurriculars that incorporate physicalactivity, like sports clubs.
Keywords: Physical activity, students, Hanoi Medical University.